2018
DOI: 10.1111/1365-2435.13219
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient addition affects scaling relationship of leaf nitrogen to phosphorus in Arabidopsis thaliana

Abstract: Ambient nutrient changes influence the coupling of nitrogen (N) and phosphorus (P) in terrestrial ecosystems, but whether it could alter the scaling relationship of plant leaf N to P concentrations remains unclear. Here, we conducted experimental manipulations using Arabidopsis thaliana, with five levels of N and P additions and nine repeated experiments, and then evaluated the changes in the scaling relationship of leaf N to P concentrations under nutrient additions. Overall, leaf N concentration scaled as 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 49 publications
(130 reference statements)
0
3
0
1
Order By: Relevance
“…There have been conflicting results for the relationship between N and P availability and the scaling exponent. For instance, Townsend et al (2007) found that plants living in more P-limited soil had a higher exponent in the tropics; Zhang, Yan, et al (2018) found in a controlled experiment that P addition led to a lower exponent but N addition did not make a difference; and Tian et al Ågren (2008) and Yan et al (2018) both found that the limitation of one nutrient raised the relative accumulation rate of that nutrient compared to the other. We conclude that these are two different types of adaptive responses to nutrient limitation.…”
Section: The Influence Of Nutrient Limitation On the N-p Scaling Rementioning
confidence: 99%
See 1 more Smart Citation
“…There have been conflicting results for the relationship between N and P availability and the scaling exponent. For instance, Townsend et al (2007) found that plants living in more P-limited soil had a higher exponent in the tropics; Zhang, Yan, et al (2018) found in a controlled experiment that P addition led to a lower exponent but N addition did not make a difference; and Tian et al Ågren (2008) and Yan et al (2018) both found that the limitation of one nutrient raised the relative accumulation rate of that nutrient compared to the other. We conclude that these are two different types of adaptive responses to nutrient limitation.…”
Section: The Influence Of Nutrient Limitation On the N-p Scaling Rementioning
confidence: 99%
“…Some studies found that the value of β was generally affected by the P availability and that an enhanced P supply led to a lower β, that is, a higher relative P accumulation rate ( Figure 1a; Tian et al, 2018;Townsend, Cleveland, Asner, & Bustamante, 2007;Zhang, Yan, et al, 2018). On the other hand, a few studies suggested the increased relative accumulation rate of the more limited element (Ågren, 2008;Yan et al, 2018). For instance, an undersupply of N gives rise to a higher β, but an undersupply of P causes a lower β (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…The numbers out-and inside parentheses represent the numbers of observations for experiments in natural and controlled environments, respectively. Ostertag, 2010; Mayor et al, 2014; Sardans et al, 2017)。总体上, 施 N对草本植物和林下植物N和P计量特征的影响更加 显著(Tian et al, 2017; Zhan et al, 2017); 衰老叶片、 茎、根系N和P含量对施N的响应很可能比新鲜叶片 更敏感(Schreeg et al, 2014)。 结合外在环境条件和内在生理机制进行综合分 析, 可以概括为如下结论: 自然生态系统中植物器 官N和P计量特征对施N的差异性响应与生态系统原 本的养分可利用性、N和P限制状况以及物种的化学 计量内稳性有关(Sistla & Schimel, 2012; Yu et al, 2015; Yue et al, 2017)。 例如, 在热带低地森林, 施N 没有改变叶片N含量, 但是施P会提高叶片P含量, 降低N:P (Mayor et al, 2014), 这很可能与热带森林 生 态 系统 普遍 受 P 限制的 特 点有 关(Deng et al, 的趋势, P含量呈现先下降后趋于稳定不变的趋势, 且这种交互影响在拟南芥不同生育期和不同器官间 存在明显差异(Yan et al, 2015(Yan et al, , 2016a(Yan et al, , 2018(Yan et al, , 2019 关系的假说, 包含生长速率假说(Sterner & Elser, 2002), N:P阈值假说(Koerselman & Meuleman, 1996;Güsewell, 2004), N-P计量关系的幂指数法则(Niklas et al, 2005;Reich et al, 2010), 生产力-养分分配假 说和生产力-叶片寿命假说(Tang et al, 2018); (2)环 境关联假说或理论, 即刻画化学计量特征与环境因 子之间关系的多种假说, 包含化学计量内稳性理论(Sterner & Elser, 2002), 限制元素稳定性假说(Han et al, 2011), 叶片养分含量稳定假说(Tang et al, 2018), 温度-生物地球化学假说)和 温度-植物生理假说, 土壤 基质年龄假说)和相对重吸 收假说(Han et al, 2013); (3)进化关联假说, 即刻画 化学计量特征与植物进化历史关系的假说, 包含物 种组成假说, 常绿-落叶假 说, 生物地球化学生态位假 说(Peñuelas et al, 2008(Peñuelas et al, , 2019 & Cobb, 2005;Elser et al, 2010), 但也有研究认为生长速率假说的适用性需要考虑养 图3 植物生态化学计量学的主要理论和假说。 这些理论和假说主要包含3类: (1)功能关联假说(蓝色标注), (2)环境关联理论和 假说(棕色标注), (3)进化关联假说(绿色标注)。图中卡通图和谱系树图于2020年12月10日引自Google图片网站。 Fig.3Main theories and hypotheses in plant stoichiometry. Three categaries are included: (1) function-associated hypotheses (annotated in blue), (2) environment-associated hypotheses (annotated in brown), and (3) evolution-associated hypotheses (annotated in green).…”
unclassified
“…Accordingly, the concentrations and stoichiometric ratio of N and P in plants are widely used to reflect the plant nutrient status and nutrient supply of ecosystems (Sardans and Peñuelas, 2012). Notably, many previous studies have focused on green leaves (Mayor et al, 2014;Yan et al, 2018;Liu et al, 2021). Leaf nutrient dynamics are a more reliable indicator of plant adaptive strategies than total nutrient concentrations (Yang, 2018;Xu et al, 2021); moreover, their species-specific responses could explain the changes in community structure (Wan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%